2006
DOI: 10.1007/s11604-005-0028-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic arterial supply to the normal basal segments of the left lower lobe treated by coil embolization, with long-term follow-up

Abstract: We report a case of a 41-year-old woman who underwent therapeutic embolization of an aberrant systemic artery of the lung. Except for chest pains immediately after embolization, she recovered well and has not experienced hemoptysis in the past 6 years. In such patients, coil embolization could be an alternative choice of treatment, with the expectation of an excellent long-term result despite ischemia of the corresponding lung parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 12 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…6,7,11 No cases of ASALLL with dual supply, rightsided anomalies, anomalous vessels arising from the coeliac axis or abdominal aorta were documented in the present study. All of 16 cases of ASALLL in the present study were supplied solely by the isolated systemic artery, as was the case in previous published reports.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…6,7,11 No cases of ASALLL with dual supply, rightsided anomalies, anomalous vessels arising from the coeliac axis or abdominal aorta were documented in the present study. All of 16 cases of ASALLL in the present study were supplied solely by the isolated systemic artery, as was the case in previous published reports.…”
Section: Discussionmentioning
confidence: 52%
“…4,5 These procedures could shorten the hospitalization time. 4e6 Saida et al 6 reported that satisfactory clinical results were obtained in patients after 6 years of observation. It is essential to distinguish ASALLL from PS because the outcome of ligation, anastomosis, and embolization was not different from that of lobectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The number of coils used in our cases was minimal, and the long-term outcome is unknown. In cases of systemic arterial supply to the basal segments of the lower lobe without sequestration, therapeutic transarterial embolization without lung resection can be an alternative treatment option (11,12); however, there is no report about the same therapy in the case of sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…When employed as definitive means of treatment, angioembolization was associated with lower risk of morbidities than thoracotomy. [9][10][11] On the other hand, Diks et al reported that angiographic embolization could not achieve complete control of main complications of pulmonary sequestration: pleural pain, ischemic infarction, and abscess formation. For this reason, they maintained that surgical resection is still the most effective and definitive therapeutic strategy for this kind of lung malformation.…”
Section: Discussionmentioning
confidence: 99%